Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer:
4/3 =a
Step-by-step explanation:
10 − 3(2a − 1) = 3a + 1
Distribute
10 -6a +3 = 3a+1
Combine like terms
13 -6a = 3a+1
Add 6a to each side
13-6a+6a = 3a+6a +1
13 = 9a+1
Subtract 1 from each side
13-1 = 9a+1-1
12 = 9a
Divide by 9
12/9 = 9a/9
4/3 =a
Answer:
a = 4/3
Step-by-step explanation:
10 - 3( 2a - 1 ) = 3a + 1
- use the distributive property to multiply -3 by 2a -1
10 - 3 × 2a -3 × -1 = 3a + 1
10 - 6a + 3 = 3a + 1
- collect like terms
10 + 3 - 6a = 3a + 1
13 - 6a = 3a + 1
- Subtract 3a from both sides
13 - 6a - 3a = 3a - 3a + 1
13 - 9a = 1
- subtract 13 from both side
13 - 13 - 9a = 1 - 13
- 9a = - 12
- divide both side by -9
-9a / - 9 = - 12 / - 9
a = 4/3
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.